"This is a Learning Opportunity": How Parent–Child Interactions and Exhibit Design Foster the Museum Learning of Prior-to-School Aged Children. Issue 2 (3rd July 2019) - Degotardi, Sheila; Johnston, Kelly; Little, Helen; Colliver, Yeshe; Hadley, Fay
Abstract: Recent research indicates that museums hold great potential for children's engagement and learning. To date, most research has either focused on school-aged children or young children's independent learning engagement and, as a result, little research has investigated how museum spaces may foster and enhance the interactive learning of families with prior-to-school-age children. The current study sought to investigate which features of museum spaces might promote rich learning conversations within such families when visiting three metropolitan museums. Applying an interpretivist lens on video data generated from child and parent videos, and analyzing postvisit interview data, this study found shared attention, questioning, technical vocabulary, and cognitive connections featured in the learning conversations in such spaces. Further, intricate detail, different perspectives, interactivity and multimodality were significant exhibit design features that appeared to promote such learning conversations. Implications for exhibit design are discussed in relation to the undergirding concept of sustained shared thinking.